1989
DOI: 10.1017/s000748530001837x
|View full text |Cite
|
Sign up to set email alerts
|

A simulation model describing the population dynamics and damage potential of the rose grain aphid, Metopolophium dirhodum (Walker) (Hemiptera: Aphididae), in the UK

Abstract: Metopolophium dirhodum (Walker) is occasionally a pest of cereals in the UK. A simulation model was developed to study its population dynamics and damage potential. The model was initiated by aphid immigration as measured by 12-2-m suction trap samples and with temperature as the major driving variable. It was validated with field observations from three contrasting years, 1979, 1985 and 1986. The model accurately predicted aphid populations and yield loss in a major outbreak year (1979) but was less accurate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

1991
1991
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 11 publications
0
14
0
Order By: Relevance
“…Previous studies on model organisms are mainly based on daily average temperatures, which either overlook daily maximum temperature (Rossberg et al, 1986;Freier et al, 1996;Tobin et al, 2008) or use the mean of the daily average and daily maximum temperatures (van Asch et al, 2007), and thus may underestimate the adverse impact of daily maximum temperature. By contrast, model predictions based on hourly or two-hourly average temperature (Carter et al, 1982;Zhou et al, 1989;Triltsch et al, 1998) focus on the immediate effect of temperature extremes rather than allowing for recovery at other times of the day, and thereby may overestimate the detrimental effect of daily maximum temperature. Our results may be useful for improving population dynamics prediction, as in the case of the aphid Metopolophium dirhodum (Ma, 2000).…”
Section: Population Predictions and Climate Changementioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies on model organisms are mainly based on daily average temperatures, which either overlook daily maximum temperature (Rossberg et al, 1986;Freier et al, 1996;Tobin et al, 2008) or use the mean of the daily average and daily maximum temperatures (van Asch et al, 2007), and thus may underestimate the adverse impact of daily maximum temperature. By contrast, model predictions based on hourly or two-hourly average temperature (Carter et al, 1982;Zhou et al, 1989;Triltsch et al, 1998) focus on the immediate effect of temperature extremes rather than allowing for recovery at other times of the day, and thereby may overestimate the detrimental effect of daily maximum temperature. Our results may be useful for improving population dynamics prediction, as in the case of the aphid Metopolophium dirhodum (Ma, 2000).…”
Section: Population Predictions and Climate Changementioning
confidence: 99%
“…Temperature fluctuations that vary in amplitude to approximate extremes in nature depress fitness components such as development, survival and fecundity (Ragland and Kingsolver, 2008;Paaijmans et al, 2010;Carrington et al, 2013;Xing et al, 2014), pointing to adverse effects of T max on organism performance. However, predictions based on short periods of high-temperature stress may neglect the effect of mild night-time temperatures (Carter et al, 1982;Zhou et al, 1989;Triltsch et al, 1998), which allow organisms sufficient time to recover during intervals of successive episodes of thermal stress (Davis et al, 2006;Sentis et al, 2013). Regimes used in previous studies on temperature fluctuations (reviewed by Colinet et al, 2015) tend to focus on the amplitude of fluctuating conditions and confound changes in T max with different daily minima, which also affect performance (Zhao et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Woiwod & Choppin de Janvry, 1980;Leather 8: Walters, 1983). Zhou. Carter & Mumford (1989) have developed a simulation inodcl, predicting yield losses from the rose-grain aphid.…”
Section: Introductionmentioning
confidence: 99%
“…Although the study of Dean (1974) was comprehensive enough for use in a simulation model, it was done on barley leaf discs, so these data could not be used directly in the model developed by Zhou, Carter & Mumford (1989) to study the population development of M. dirhodum on winter wheat. Other laboratory studies on barley (Dean, 1973;Wratten, 1977;Thornback, 1983), wheat (Dean, 1974;Thornback, 1983) and oats (Dean, 1973) are valuable in comparing aphid performances under different conditions but as they were done at only one temperature, their usefulness in the development of the simulation model is reduced.…”
Section: Introductionmentioning
confidence: 99%
“…These two field studies are important in understanding the biology of the aphid under field conditions, but it was not possible to obtain data of the appropriate type for the temperature-and crop growth stage-dependent development and reproductive rates to be used in the simulation model. Furthermore, the results from all of these studies varied considerably and had to be modified before being incorporated in the model as described by Zhou et al (1989). Sensitivity analyses from the model also indicated that development, reproductive and survival rates were important in affecting the population dynamics of M. dirhodum (Zhou, 1990).…”
Section: Introductionmentioning
confidence: 99%